New perspectives on Microsoft Excel 97 : introductory - Parsons, June Jamrich. (Course Technology, 1997)
This book is divided into seven parts: Using Worksheets to Make Business Decisions; Creating a Worksheet; Developing a Professional-Looking Worksheet; Creating Charts; Working with Excel Lists; Integrating Excel with Other Windows Programs and the World Wide Web; Developing an Excel Application.